IMPROVEMENT OF THE EVALUATION SYSTEM OF JUDGES' PERFORMANCE IN UZBEKISTAN - Sherbadalov Ravshanbek Tursunovich (Web of Journals Publishing, 2025)
In this article, the procedure and criteria for evaluating the effectiveness of judges in the Republic of Uzbekistan, their current state, the urgency of their improvement, the experience of foreign countries on the system of evaluating the effectiveness of employees, the suggestions for improving the procedure and criteria for evaluating the effectiveness of judges and their relevance are considered.
Keywords: Evaluation of the effectiveness of judges, electronic information system of justice, corps of judges, justice, evaluation criteria, quantitative analysis, qualitative analysis.